Dampak Globalisasi pada Konten dan Mata Pelajaran Pada Kurikulum di Madrasah Ibtidaiyah: Tantangan Dan Peluang - Sulaiman Kurdi, Muqarramah (Lembaga Pengembangan Kinerja Dosen, 2021)
This research elucidates the impact of globalization on the content and subjects of the Madrasah Ibtidaiyah curriculum, focusing on the challenges and opportunities it presents. The study utilizes a combination of literature review and thematic analysis to explore the influence of globalization on the curriculum and the strategies employed by Madrasah Ibtidaiyah to strike a balance between traditional Islamic teachings and global knowledge and skills. The findings reveal that globalization has influenced the content and subjects taught in the Madrasah Ibtidaiyah curriculum by necessitating the incorporation of global perspectives, emphasizing universal values, and contextualizing global knowledge within an Islamic framework. However, Madrasah Ibtidaiyah faces challenges in adapting its curriculum, including the need to ensure the preservation of Islamic teachings, address cultural sensitivities, and navigate societal expectations. Despite challenges, globalization offers opportunities for Madrasah Ibtidaiyah to enhance its curriculum and prepare students for a globalized world. This includes fostering intercultural communication, promoting global citizenship, encouraging critical thinking, nurturing tolerance and inclusion, and developing cultural sensitivity. The incorporation of global perspectives significantly impacts students' understanding of diversity and multiculturalism by exposing them to different cultures, challenging stereotypes, promoting intercultural communication, and fostering a sense of global citizenship.